PENGARUH BEBERAPA KONSENTRASI SITOKININ TERHADAP PEMBENTUKAN BUAH PARTENOKARPI PADA TANAMAN CABAI (Capsicum annum L.) - Rahmayani, Elva; Rizki, Rizki; Novi, Novi (Pendidikan Biologi, 2013)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â  Chili of cultivation will be attracted for most of farmers because the highest economic value. It influences by the quality of chili it self. Nowadays, the quality of chiliâs cultivation is still low. One of the way to solve this problem is partenocarpy. This research aims ti know the effect some cytokinin concentrate to establish the chiliâs fruit (Capsicum annum L.). the research has done on February until August in 2013 in Green House of Biology, Science and Math Faculty, UNAND by using RAL (Random design complete) with 6 treatmenst and 4 repetations. The control without, cytokinin concentrate 20 ppm, 40 ppm, 60 ppm, 80 ppm, and 100 ppm. The result of this research shows that giving concentrate 80 ppm is the best in avolding seeds with average 5,25 seeds, 100 ppm for size, diameter, and weight of the chili.Â